(untitled) (Agricultural Engineering, 2017)
In recent years systemic changes in waste management have affected searching and implementation of solutions that increase waste recovery including those intended for recycle. The article presents a predicted amount of municipal waste intended for recovery based on their selected streams. For the needs of a conceptual solution the area was determined, which was operated by the mentioned installation. The paper uses the indicators of waste accumulation: mass, volume, bulk density and irregularity of their collection in 2011-2013 for determination of the sorting plant efficiency. Elements of the installation, which should enable optimization of the waste recovery process optimization, were selected. Moreover, frames of technological efficiency of the suggested solution were defined. The aim of the paper was an attempt to select parameters of a municipal waste sorting plant with location under conditions of Stary Sącz city.